(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
The meeting between Modern Movement and Italian urban culture is, even today, an extraordinary place for reflection on urban space, its transformation and its possibilities, its beeing a "model city" (città dimostrativa). The modern city is above all an idea of the city. The proposed reflection regards the city as a field of refoundation in which it is essential to have a completely specific refounding principle for Italy on the international scene, which derives from the cultural context and the link between the project and the original dimension of the places.